A Novel Excavation and Construction Method for an Extra-Long Underwater Tunnel in Soft Soils - Jian Wu (Hindawi Limited, 2021)
The cut-and-cover technique is widely used in the field of tunnel engineering owing to its simple construction technology, high working efficiency, and low cost. However, the safety of the foundation pit and the environmental impact during excavation are of great concern, especially for tunnels that pass through lakes and/or rivers. In this paper, a novel excavation and construction method is presented for the Taihu tunnel, which is the longest lake-crossing tunnel in China. In this method, a cofferdam of double-row steel sheet piles (DSSPs) was designed in order to divide the overlying excavation into several closed zones. During the construction, four zones were regarded as a unit, and different construction steps were carried out simultaneously in each zone. Therefore, an assembly line for the tunnel excavation was established to accelerate the construction speed. The most distinctive advantage of this method is that the excavation did not cut off the normal flow of the lake water and the shipping routes, with low environmental impact. To investigate the tunnel deformation during excavation, a finite element analysis combined with field monitoring data was adopted, indicating that the magnitude of the tunnel deformation was notably less than those reported from other excavation projects. Moreover, the effect of groundwater on the piles and the safety of the foundation pit was revealed using numerical modelling. This study provides a new idea for the design and construction of tunnel engineering, especially for extra-long underwater tunnels in soft deposits.